Removal of Rh 6G and DB 71 Dyes from Aqueous Solution with High Efficiency via Adsorption on Mesoporous Silica Nanoparticles - Adel, zahraa; Hussein, Ennas Abdul (Iraqi Journal of Science, 2026)
The use of mesoporous silica to remove cationic and ionic dyes from aqueous solutions has been investigated. This is a crucial process, as these dyes are widely recognized as a significant water pollutant, posing a threat to aquatic life, human health, and agricultural productivity. Cetyltrimethylammonium bromide (CTAB) served as a template and sodium silicate, a cost-effective silica precursor, was used in the Sol-gel process. The silica particles were characterized using N2 adsorption–desorption isotherms, TEM, XRD, and SEM. The results indicate that mesoporous silica (MPS) particles in the nano range (40-80 nm) have the form of flower particles, with an average pore width of 3.44 nm, a precise surface area of 423.52 m2g-1, and a pore volume of 0.5677 cm3/g. These particles may effectively adsorb dyes. The Langmuir, Freundlich, and Timken models of adsorption suited the adsorption equilibrium data, and the best-fitting isotherm model was determined using the linear regression coefficient R2. A variety of thermodynamic parameters have also been assessed, including standard enthalpy change, entropy, and Gibb’s free energy of the ongoing process of adsorption. The exothermic adsorption process was spontaneous, according to the thermodynamic data. The two dyes exhibited different kinetics: Direct Blue 71 (DB71) followed pseudo-first-order kinetics, while Rhodamine 6G (Rh6G) adhered to dye and pseudo second order rate kinetics. Kinetic data were obtained using a batch approach.